(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Women artists from the Yuyachkani Cultural Group of Peru have been interested in the scenic practices developed in feminist artivism. We interviewed actress Ana Correa who told us about social intervention actions in different communities and collectives of women in Peru, about artistic-pedagogical practices to rescue memory, about the fight for the rights of women and girls who demand justice against hegemonic violence and patriarchal.